Analysis Of The Factors Determining The Success Of Micro, Small And Medium Enterprises (MSMES) In The Halal Industry In Medan City - Muhammad Qomaruz Zaman; Waizul Qarni; Rahmi Syahriza (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purpose: This study aims to analyze the factors determining the success of MSMEs in the halal industry in Medan City. Methods: Using a qualitative approach, the research explores the experiences and strategies of MSME actors in managing their businesses. Results: The findings indicate that the success of halal industry MSMEs is influenced by product innovation, the use of digital technology in marketing, and effective financial management. Government support through training, subsidies, and promotions also plays a significant role in enhancing competitiveness. Other factors, such as strategic business location and halal certification, significantly impact success. Implications: This study is expected to contribute to the development of theories and practices in the halal MSME sector Halal Industry Business Success, MSMEsand serve as a guide for stakeholders in advancing the halal industry in Medan City.